# |
ODE |
Mathematica |
Maple |
\[
{}\frac {2 t}{t^{2}+1}+y+\left ({\mathrm e}^{y}+t \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}-2 x -y \cos \left (x y\right )+\left (2 y-x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-4 x^{3}+6 y \sin \left (6 x y\right )+\left (4 y^{3}+6 x \sin \left (6 x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y+t^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 \,{\mathrm e}^{t}+4 t \right )+3 \left ({\mathrm e}^{t}+t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (2 t -y \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+y^{2}-t^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 t^{2}+\left (t^{2} y-t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 t y+4 y^{2}+1+\left (t^{2}+2 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 t y^{2}+y+\left (2 t^{3}-t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\tan \left (y\right )+\left (t -t^{2} \tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -y^{2} \sin \left (t y\right )+\left (\cos \left (t y\right )-t y \sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-1+{\mathrm e}^{t y} y+y \cos \left (t y\right )+\left (1+{\mathrm e}^{t y} t +t \cos \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +2 y+\left (2 t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {9 t}{5}+2 y+\left (2 t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\frac {19 y}{10}+\left (\frac {19 t}{10}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = \frac {t}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t y^{2}
\] |
✓ |
✓ |
|
\[
{}2 t y^{\prime }-y = 2 t y^{3} \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-y = t y^{3} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = \frac {\cos \left (t \right )}{\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \sqrt {y}\, \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \frac {y^{2}}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \frac {y^{2}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = t^{2} y^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (\frac {t}{y+t}\right )+{\mathrm e}^{\frac {2 y}{t}} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (\frac {t}{y}\right )+\frac {t^{2} y^{\prime }}{y+t} = 0
\] |
✓ |
✓ |
|
\[
{}2 \ln \left (t \right )-\ln \left (4 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2}{t}+\frac {1}{y}+\frac {t y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {\sin \left (2 t \right )}{\cos \left (2 y\right )}+\frac {\ln \left (y\right ) y^{\prime }}{\ln \left (t \right )} = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\left (y-3 t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y-3 t +t y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t y-y^{2}+t \left (t -3 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2}+t y+y^{2}-t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{3}+y^{3}-t y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t +4 y}{4 t +y}
\] |
✓ |
✓ |
|
\[
{}t -y+t y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (y+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2}-7 t y+5 y^{2}+t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 \sqrt {t^{2}+y^{2}}-t y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} = \left (t y-4 t^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y-\left (3 \sqrt {t y}+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}-y^{2}\right ) y^{\prime }+y^{2}+t y = 0
\] |
✓ |
✓ |
|
\[
{}t y y^{\prime }-t^{2} {\mathrm e}^{-\frac {y}{t}}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\frac {2 y \,{\mathrm e}^{-\frac {t}{y}}}{t}+\frac {t}{y}}
\] |
✓ |
✓ |
|
\[
{}t \left (\ln \left (t \right )-\ln \left (y\right )\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = t^{2} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = t^{2} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 y^{2}-t^{2}}{2 t y}
\] |
✓ |
✓ |
|
\[
{}t +y-t y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-y-\sqrt {t^{2}+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}t^{3}+y^{2} \sqrt {t^{2}+y^{2}}-t y \sqrt {t^{2}+y^{2}}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}-t^{3}-t y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t y^{3}-\left (t^{4}+y^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4}+\left (t^{4}-t y^{3}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}t -2 y+1+\left (4 t -3 y-6\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 t +2 y+1+\left (2 t +y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t -y+1-\left (6 t -2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +3 y+1+\left (4 t +6 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 y}{x} = -x^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = y^{4}
\] |
✓ |
✓ |
|
\[
{}y = t \left (y^{\prime }+1\right )+2 y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}t^{{1}/{3}} y^{{2}/{3}}+t +\left (t^{{2}/{3}} y^{{1}/{3}}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}-t^{2}}{t y}
\] |
✓ |
✓ |
|
\[
{}y \sin \left (\frac {t}{y}\right )-\left (t +t \sin \left (\frac {t}{y}\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 t^{5}}{5 y^{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (4 x \right )-8 \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \frac {y^{2}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{8 y}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{5 t}}{y^{4}}
\] |
✓ |
✓ |
|
\[
{}-\frac {1}{x^{5}}+\frac {1}{x^{3}} = \left (2 y^{4}-6 y^{9}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \,{\mathrm e}^{-2 t}}{\ln \left (y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (4-7 x \right ) \left (2 y-3\right )}{\left (x -1\right ) \left (2 x -5\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = -10 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}3 t +\left (t -4 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-t +\left (y+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-x +y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (t y+t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}r^{\prime } = \frac {r^{2}+t^{2}}{r t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {5 t x}{t^{2}+x^{2}}
\] |
✓ |
✓ |
|
\[
{}t^{2}-y+\left (-t +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y+\sin \left (t \right )+\left (\frac {t^{3}}{3}-\cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\tan \left (y\right )-t +\left (t \sec \left (y\right )^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t \ln \left (y\right )+\left (\frac {t^{2}}{2 y}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 5
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+t y = t
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+\frac {x}{y} = y^{2}
\] |
✓ |
✓ |
|
\[
{}t r^{\prime }+r = \cos \left (t \right ) t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = t y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {{\mathrm e}^{t}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}y-t y^{\prime } = 2 y^{2} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}2 x -y-2+\left (-x +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (t -y\right )+\left (1-\cos \left (t -y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t y} y-2 t +t \,{\mathrm e}^{t y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )-y \cos \left (t \right )+\left (t \cos \left (y\right )-\sin \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (2 t y-2 \cos \left (y\right ) \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{t}+\ln \left (y\right )+\left (\frac {t}{y}+\ln \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-x
\] |
✓ |
✓ |
|